SIKAP MASYARAKAT DALAM PENGELOLAAN HUTAN PASCA KEGIATAN REBOISASI DI KELURAHAN LAMBARA KECAMATAN PALU UTARA KOTA PALU - Rusdiana Rusdiana; Adam Malik; Sitti Ramlah (Jurnal Warta Rimba, 2017)
This research aimed to find out people‘s will level about reforestation in Lambara. This research was conducted on September up to the month of November 2014, it was located in Lambara, North Palu, Palu City. This research used data type and data source, data gathering technique, data analysis by using Likert Scale.  The result of the research showed that age, educational background, dependents, income, and land size that possessed by respondents were low.  The people’s will about reforestation, the lack of understanding about reforestation was low enough, but people understanding about reforestation was  high because of the socialization given by the person on charge in Lambara that tent to the way doing reforestation, the plants grown, the planting space, and the plants treatment. The people’ will about reforestation in Lambara was low enough.  The lack of understanding and knowledge about reforestation in Lambara was affected by educational background and socialization about reforestation that was done by person in charge to the people of Lambara was less. Therefore in the recent time no more reforestation activities done because most of the people there work on the plantation.Kata Kunci: People’ attitude, forest management, Reforestation